2022
DOI: 10.4103/1673-5374.320969
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecapeptide BPC 157 and the central nervous system

Abstract: We reviewed the pleiotropic beneficial effects of the stable gastric pentadecapeptide BPC 157, three very recent demonstrations that may be essential in the gut-brain and brain-gut axis operation, and therapy application in the central nervous system disorders, in particular. Firstly, given in the reperfusion, BPC 157 counteracted bilateral clamping of the common carotid arteries-induced stroke, sustained brain neuronal damages were resolved in rats as well as disturbed memory, locomotion, and coordination. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
162
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(162 citation statements)
references
References 54 publications
0
162
0
Order By: Relevance
“…The stable gastric pentadecapeptide BPC 157 was chosen and tested in this study due to its beneficial effects in major vessel occlusion syndromes ( Vukojevic et al, 2018 ; Gojkovic et al, 2020 ; Kolovrat et al, 2020 ; Gojkovic et al, 2021a ; Knezevic et al, 2021a ; Knezevic et al, 2021a ; Gojkovic et al, 2021b ; Knezevic et al, 2021b ; Strbe et al, 2021 ) and as a prototypic cytoprotective peptide (for review, see Sikiric et al, 1993a ; Sikiric et al, 2006 ; Sikiric et al, 2010 ; Sikiric et al, 2011 ; Sikiric et al, 2012 ; Sikiric et al, 2013 ; Sikiric et al, 2014 ; Sikiric et al, 2016 ; Sikiric et al, 2017 ; Sikiric et al, 2018 ; Sikiric et al, 2020a ; Sikiric et al, 2020b ; Seiwerth et al, 2014 ; Seiwerth et al, 2018 ; Seiwerth et al, 2021 ; Kang et al, 2018 ; Park et al, 2020 ; Gwyer et al, 2019 , Vukojevic et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable gastric pentadecapeptide BPC 157 was chosen and tested in this study due to its beneficial effects in major vessel occlusion syndromes ( Vukojevic et al, 2018 ; Gojkovic et al, 2020 ; Kolovrat et al, 2020 ; Gojkovic et al, 2021a ; Knezevic et al, 2021a ; Knezevic et al, 2021a ; Gojkovic et al, 2021b ; Knezevic et al, 2021b ; Strbe et al, 2021 ) and as a prototypic cytoprotective peptide (for review, see Sikiric et al, 1993a ; Sikiric et al, 2006 ; Sikiric et al, 2010 ; Sikiric et al, 2011 ; Sikiric et al, 2012 ; Sikiric et al, 2013 ; Sikiric et al, 2014 ; Sikiric et al, 2016 ; Sikiric et al, 2017 ; Sikiric et al, 2018 ; Sikiric et al, 2020a ; Sikiric et al, 2020b ; Seiwerth et al, 2014 ; Seiwerth et al, 2018 ; Seiwerth et al, 2021 ; Kang et al, 2018 ; Park et al, 2020 ; Gwyer et al, 2019 , Vukojevic et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…BPC 157 acts as a membrane stabilizer and free radical scavenger and reduces leaky gut syndrome, as shown in gastrointestinal tract cytoprotective studies ( Park et al, 2020 ). BPC 157 also has a curative effect due to interactions with several molecular pathways ( Tkalcević et al, 2007 ; Chang et al, 2011 , 2014 ; Huang et al, 2015 ; Hsieh et al, 2017 ; Kang et al, 2018 ; Vukojevic et al, 2018 ; Wang et al, 2019 ; Cesarec et al, 2013; Hsieh et al, 2020 ; Park et al, 2020 ; Vukojevic et al, 2020 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be highlighted that the results of animal studies per se should be interpreted cautiously, particularly those from lithium studies [ 17 ] (note, the original Cade study used a 0.5% lithium solution in guinea pigs) [ 109 ]. Similarly, there is a relative paucity of clinical data on BPC 157 [ 10 , 11 , 12 , 13 , 14 ]. Nonetheless, BPC 157 has been proven to be efficacious in the treatment of ulcerative colitis, both in clinical settings [ 110 , 111 ] and in experimental rats with ulcerative colitis in ischemic/reperfusion studies [ 21 ] and other ulcerative colitis models, including various species [ 85 , 86 , 87 , 88 , 89 , 90 , 101 , 112 , 113 ] and complications (for a review see [ 114 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that the stable gastric pentadecapeptide BPC 157 (for a review see [ 10 , 11 , 12 , 13 , 14 ]) may counteract the adverse effects of the administration of a huge dose of lithium sulfate (500 mg/kg ip) in rats [ 15 ]; dose selection in accordance to the counteracted magnesium-high dose toxicity [ 16 ] showed that many direct targets of lithium are likely magnesium-dependent intracellular enzymes [ 17 ]. Otherwise, an immediate severe syndrome was produced (severe muscular weakness and prostration, reduced muscle fibers, myocardial infarction, and edema of various brain areas (with the most prominent being in the cerebral cortex)) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation